Disaster preparedness analysis at Rajawali Citra General Hospital using the hospital safety index framework - Rifky Rusmasatya; Maria Ulfa (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Hospitals are vital facilities that must remain operational during disasters. However, many hospitals in Indonesia continue to face challenges in ensuring adequate preparedness in structural, non-structural, and emergency management. The Hospital Safety Index (HSI) is an important tool for assessing these preparedness levels, yet empirical evaluations of regional hospitals remain limited. Objective: To analyze the disaster preparedness level of Rajawali Citra General Hospital using the HSI framework to evaluate the resilience of healthcare facilities. Methods: A quantitative, descriptive–analytical design was employed, involving 28 respondents selected through total sampling from staff members involved in the hospital’s safety system. Data were collected using a Google Form-based questionnaire measuring the three main HSI dimensions: structural safety, non-structural safety, and emergency management. Statistical analysis was conducted using SmartPLS, including validity and reliability testing and structural model analysis to assess the contribution of each dimension to the hospital safety index. Results: Structural safety (coefficient 0.792) is the most dominant component influencing the HSI at Rajawali Citra General Hospital. In contrast, non-structural safety (coefficient–0.058) and emergency management (coefficient 0.100) demonstrate weaker effects, suggesting the need for improvements in facility conditions, operational systems, and emergency response procedures. Conclusion: Overall, the study highlights that hospital preparedness remains suboptimal. Therefore, a more holistic development of the HSI requires balancing physical, organizational, and human resource factors. These findings can serve as a reference for policymakers and hospital administrators in designing mitigation strategies to strengthen healthcare system resilience and ensure optimal hospital functionality during disasters.